Management of hematological malignancies in patients affected by renal failure. Issue 3 (March 2011) - Niscola, Pasquale; Vischini, Gisella; Tendas, Andrea; Scaramucci, Laura; Giovannini, Marco; Bondanini, Francesco; Romani, Claudio; Brunetti, Gregorio Antonio; Cartoni, Claudio; Cupelli, Luca; Ferrannini, Michele; Perrotti, Alessio; et al.
The management of hematological malignancies (HM) in renally impaired patients may be a difficult task. Indeed, the kidney represents a major elimination pathway for many chemotherapeutic agents and their metabolites, whose serum levels are not usually measured in daily clinical practice. In addition, many antineoplastic drugs have a narrow therapeutic index for which they require dose adjustment when administered to patients with renal failure. Only limited data regarding the use of chemotherapy in patients with renal impairment and in those on dialysis are available. Indeed, renal patients with HM are often excluded from most clinical trials. Thus far, in order to provide recommendations, we have reviewed the pertinent literature, gathering information from published guidelines regarding chemotherapy in patients with kidney dysfunction and from articles describing the use of individual agents in renal patients with HM.